A model to determine the need to modernise the regulation of the principle of utmost good faith. Issue 4 (3rd July 2021) - Farrugia, Andre; Grima, Simon
Abstract : Purpose: The purpose of this paper is to determine and lay out the variables that influence countries to carry out regulatory modernisation of the regulation of the principle of good faith in insurance so as to ensure standardisation of its application and to reduce regulatory asymmetries and uncertainties in the handling of this requirement, given the fast pace of changes in the current ecosystem. Moreover, the authors show whether these variables differ, given the different demographic factors of the respondents participating in this research. Design/methodology/approach: To collect the research data, which consisted of 1, 794 valid responses, the authors administered a purposely built survey, which they designed after carrying out and extensive literature search, which yielded 3, 248 valid records and resulted in the inclusion of 27 research articles through a scoping review after considering inclusion/exclusion criteria (i.e. the Preferred Reporting Items for Systematic Reviews and Meta-Analysis) search strategy. The authors carried this survey between September 2019 and June 2020 using the social network, verbal and online communication systems. The survey was addressed to persons within insurance associations, professional members, persons within large corporates in the insurance industry and selected experts in the field who were purposely selected based on the work experience held, roles occupied in the industry, qualifications attained and area of expertise. The quantitative data was analysed using statistical tools, specifically descriptive statistics, exploratory factor analysis, Cronbach's alpha and multiple linear regression. The qualitative data obtained was analysed using the thematic approach. Findings: The authors found that four variables determine the need for modernisation of the principle of utmost good faith requirement, specifically institutional stakeholders and the political-legal framework; the market, consumer influence and the socio-economic environment; socio-technological environment and insurance practice; and international business. Moreover, the authors found that these variables hold relationships with some demographic variables and differ with age, gender, level of education and occupation in a variety of ways. Practical implications: The statements grouped under the themes determined as influencing factor variables for the need for modernisation of the principle of utmost good faith, can be used by stakeholders such as policymakers and reformists within countries as a measure to determine whether this regulatory requirement is in need of modernisation or it can be used as a model for determining modernisation of other regulations or for the development of other similar models. Moreover, scholars may use this model for other sectors and other regulatory frameworks in different jurisdictions. Originality/value: Although, the authors have noted several articles about modernisation carried out on regulations, to the best of their knowledge, they have not encountered articles that capture the influencing factor variables for the need for modernisation of the principle of utmost good faith under a group of themes.